Propagation of Grape by Nodal Stem cuttings - Osman, Magdoleen Gamar Eldeen; Said, Abdel Gaffar Elhag; Abdalla, Hala Almobashar (University of Khartoum Journal of Agricultural Sciences, 2023)
Experiments were conducted to test the effect of MS salts concentration, potassium dihydrogen phosphate and growth regulators on shoot proliferation and growth in grapevine (Vitis vinifera L.), using explants derived from in vitro grown plantlets. Murashige and Skoog original medium was used as basal medium. Shoot proliferation occurred principally when using nodal stem segments as explants. Among MS-salt strengths tested, full MS- strength (1X) was optimum for shoot proliferation and elongation. Increasing the original phosphorus concentration in the medium by the addition of 170 mg/L KH2 PO 4 had a positive, marked effect on shoot number and shoot length. The nodal stem segment explants responded best to relatively low concentrations of NAA and kinetin, and a large number of shoots and good plantlets height were obtained on the medium containing 0.1mg/L NAA and 1.0 mg/L kinetin. Root formation occurred on the medium containing 0.3 mg/L IBA.